(untitled) (Research, Society and Development, 2021)
The use of the xenogenous collagen matrix (MCX) was investigated as an alternative for root coverage in the treatment of gingival recession, especially in areas that require an increase in keratinized tissue and in order to decrease the patient’s morbidity and surgical time. The purpose of this literature review is to analyze the use of the xenogen collagen matrix as a form of treatment for covering gingival recessions. A bibliographic search of controlled and randomized clinical trials was carried out, before 2010 to 2020, which evaluated the treatment of single or multiple gingival recession using a xenogen collagen matrix, and 14 clinical trials were selected according to the inclusion criteria. The results showed that the combination of MCX associated with coronary repositioning (CR) is a viable alternative in the treatment of gingival recession, similar results when compared to the subepithelial connective tissue graft (ETCS + RC). The use of MCX associated with CR has been effective in gaining keratinized tissue and increasing gingival thickness in the treatment of Type I (RT1) gingival recessions, and can be an alternative to ETCS in patients with limited palatal donor area and also reduce patient morbidity and operative time.